2012
DOI: 10.1038/bjc.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of ovarian cancer response to cisplatin, carboplatin, and paclitaxel identifies common pathways that are also associated with overall patient survival

Abstract: Background:Carboplatin and cisplatin, alone or in combination with paclitaxel, have similar efficacies against ovarian cancer (OVCA) yet exhibit different toxicity profiles. We characterised the common and unique cellular pathways that underlie OVCA response to these drugs and analyse whether they have a role in OVCA survival.Methods:Ovarian cancer cell lines (n=36) were treated with carboplatin, cisplatin, paclitaxel, or carboplatin–paclitaxel (CPTX). For each cell line, IC50 levels were quantified and pre-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Although the carboplatin-related compound CP- 6 was less potent than CP- 11 , it only exhibited a 1.3-2.7 fold loss in potency compared to its parent drug carboplatin, depending on the cell line (Table 1). Of note, carboplatin sensitivity observed here is highly consistent with previously published results [25] .…”
supporting
confidence: 93%
“…Although the carboplatin-related compound CP- 6 was less potent than CP- 11 , it only exhibited a 1.3-2.7 fold loss in potency compared to its parent drug carboplatin, depending on the cell line (Table 1). Of note, carboplatin sensitivity observed here is highly consistent with previously published results [25] .…”
supporting
confidence: 93%
“…It is still debated in the literature whether the CR following chemotherapy holds the same value of the CR achieved after primary surgery. Many authors suggest a disease-concealing role exerted by the neo-adjuvant chemotherapy [15][16][17][18][19][20][21]. This could disguise the real extent of disease and curtail the aggressiveness of the surgery [18].…”
Section: Discussionmentioning
confidence: 97%
“…that controls vesicle traffic within the cell (27) and members of the RAS oncogene family (11,28), MAPK14 and PDGFD (29) part of the MAPK signaling pathway (P ¼ 10 À4 ), involved in the initiation of a G 2 delay after UV radiation (30) and also identified in in vitro studies (11). Only these candidate pathways, previously associated with chemoresponse, were used in the rest of the study.…”
Section: Selection Of Candidate Pathways Associated With Chemoresponsementioning
confidence: 99%
“…In previous studies, we have identified a series of molecular signaling pathways associated with OVCA response to chemotherapy in vitro as well as in clinical settings (10)(11)(12)(13). We selected pathways associated with chemoresponse to design a pilot study aimed to identify biologic processes that influence expression.…”
Section: Introductionmentioning
confidence: 99%